ANALYSIS OF THE EFFECTIVENESS OF DIFFERENTIATED INSTRUCTION IN IMPROVING STUDENT WELL-BEING IN GRADE VII SOCIAL STUDIES LEARNING AT SMP NEGERI 1 TEGALSARI - Nanin Pasroni (Lafadz Jaya Publisher, 2023)
One of the transformations of Indonesia education through the Kurikulum Merdeka to create superior Human Resources (HR) is an educational process that places students in a safe, comfortable and happy environment. This can be realized through differentiated instruction with a learning philosophy that favors differences in students. This study aims to analyze the Effectiveness of Differentiated instructionin Improving Student Well-Being of Students in Class VII IPS Learning at SMP Negeri 1 Tegalsari. The differentiated instruction approach respects the differences of students who are very diverse and can respond to all their needs in the learning process as well as accordingly. The method in this study uses a descriptive method with a qualitative approach to analyze a phenomenon that will be examined through the support of literature studies so as to strengthen the results of the research obtained in making conclusions. data collection was carried out with a simple random sample (Simple Random Sampling). The results of this study found that out of 37 samples of class VII students at SMP Negeri 1 Tegalsari, a total of 192, after going through a differentiation learning process both in terms of content differentiation, process, product and learning environment adjusted to their level of readiness (rediness), profile and learning interest. showed very varied responses, namely: 25 students felt happy, 30 students felt comfortable, 32 students were free, 21 students were self-confident, 24 students were independent, 28 students were enthusiastic, and 31 students were communicative. students during learning. Based on the results of this study, differentiated instruction is very effective in increasing Student Well-Being in social studies learning.